1998
DOI: 10.1089/jir.1998.18.393
|View full text |Cite
|
Sign up to set email alerts
|

Effects of IFN-β on Human Cerebral Blood Flow Distribution

Abstract: The effect of interferon-beta1b (IFN-beta) on human cerebral blood flow distribution was examined in five multiple sclerosis patients using functional brain single-photon emission tomography (SPECT). Of nine regions of interest studied, only the basal ganglia exhibited a significant change (increase) in relative photon emission intensity (i.e., relative blood flow) when comparing SPECT scans obtained 6 h after s.c. IFN-beta injection with scans obtained at the same time of day (noon) 30 h after IFN-beta inject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…These investigators further showed that addition of IFN-β1b to this in vitro model inhibits the formation and transendothelial migration of the monocyte:CD31+EMP complexes. Other investigators have also demonstrated that β-interferons counteract the effects of pro-inflammatory cytokines on the integrity of the endothelial layer of the BBB and, therefore, stabilize endothelial integrity [ 22 , 23 ]. Other possible explanations for the observed effect of IFN-β1a on plasma levels of CD31+EMP involve the protective effects of β-interferons as a class on the endothelial layer of the BBB.…”
Section: Discussionmentioning
confidence: 99%
“…These investigators further showed that addition of IFN-β1b to this in vitro model inhibits the formation and transendothelial migration of the monocyte:CD31+EMP complexes. Other investigators have also demonstrated that β-interferons counteract the effects of pro-inflammatory cytokines on the integrity of the endothelial layer of the BBB and, therefore, stabilize endothelial integrity [ 22 , 23 ]. Other possible explanations for the observed effect of IFN-β1a on plasma levels of CD31+EMP involve the protective effects of β-interferons as a class on the endothelial layer of the BBB.…”
Section: Discussionmentioning
confidence: 99%
“…Although the effect of interferon beta on CVR is unknown, a study among 5 patients with MS showed that interferon beta increased blood flow in the basal ganglia. 34 Moreover, interferon beta, similar to other diseasemodifying treatment, slows the rate of brain atrophy and lesion accumulation in MS. 35 Thus, the potential relationship between CVR and brain atrophy along with lesion accumulation might be abolished by treatment with interferon beta. Third, some investigators regard breath-holding a less reliable hypercapnic stimulus than CO 2 inhalation.…”
Section: Ms Remissionmentioning
confidence: 99%
“…In a more recent study, Mackowiak et al (7) investigated the effects of single subcutaneous injection of IFN beta on cerebral blood flow (CBF) in five patients with multiple sclerosis. Utilizing single photon emission computed tomography (SPECT), the investigators demonstrated increased CBF in the basal ganglia.…”
Section: Pharmacokinetics Of Ifnsmentioning
confidence: 99%